The evolution of agricultural mechanization in Sri Lanka - Abeyratne, Fredrick; Takeshima, Hiroyuki (International Food Policy Research Institute, 2020)
Sri Lanka’s unique geography and its distinct experiences with machine use in rice and field crop production offer valuable insights into different patterns of mechanization. Rice in Sri Lanka has a substantial irrigation infrastructure, a strong plant breeding system, and historical examples of success in location-specific breeding strategies (Pain 1986). Furthermore, tractor use in rice cultivation grew very quickly, especially given the relatively small amount of arable land in the country and the lack of direct subsidies, but with certain incentives. Though mechanization initially spread for paddy cultivation, machinery has also become popular in varying degrees in the production of other field crops. This chapter explores the spread of mechanization in Sri Lanka, with a focus on the use of four- and two-wheel tractors, and combine harvesters. It first looks at the process of mechanization from a historical perspective. It then conducts demand- and supply-side analysis to identify the opportunities and challenges facing adoption of machinery in agriculture. It concludes with a brief discussion of the implications of the Sri Lankan experience for African countries starting the process of mechanization.